STUDY OF PRECIPITATION CASES USING THE WRF3 IN THE SOUTH OF BRAZIL - Yamasaki, Yoshihro (2016)
The aim of the study has been to evaluate the results of the data assimilation of INMET automatic weather stations and soundings of the southern of Brazil in precipitation and temperature forecasting of predicting of the WRF model by 3DVAR method (WRF-3DVAR), analyzing in each case, whether the WRF-3DVAR forecasts are more accurate than the WRF without data assimilation. The obtained results show the great importance of data assimilation in precipitation prediction of the WRF model. The prognoses of vertical profiles of the air and the dew point temperatures, showed that the data assimilation produced predictions with thermal and moist vertical structures more realistic in the light of the observational soundings.